Mapping Research trend in Covid 19 and energy - Marina Artiyasa; Marina; Muhammad Natsir; Panji Narputro; Dudih Gustian (INTERNATIONAL JOURNAL ENGINEERING AND APPLIED TECHNOLOGY (IJEAT), 2024)
This research  delves into the bibliometric analysis of the interconnection between COVID-19 and energy, exploring the scholarly landscape and research trends in these critical areas. By employing bibliometric methods  using biblioshiny to analyze publications, citation networks, and collaboration patterns, this study aims to uncover the impact and visibility of research  from 2020-2023 from scopus index on  keyword COVID-19 and energy. , average citation in document  is 16,54.In H index , We can see that affiliation  Energies. Have highest H index 14, the highest  no of documents belongs to Klemes JJ with 12 documents, We can see that  affiliation  from China university of Petroleum  (East China) have the highest production   article  in year  2023 reach   nearly  20. in this data china have the highest corresponding authors countries , The treemap indicates the most frequently used keywords in articles,in this dataset about covid19 and energy  we  find  Covid 19 and Energy utilization as the   most common word. in emerging or declining themes we find  covid  19, energy utilization and energy efficiency , and in motor themes  we  find human, human  and corona  virus disease 2019 , for basic themes and niche themes is empty